[18F]DPA-714 PET Imaging Reveals Global Neuroinflammation in Zika Virus-Infected Mice. - Kuszpit, Kyle; Hollidge, Bradley S.; Zeng, Xiankun; Stafford, Robert G.; Daye, Sharon; Zhang, Xiang; Basuli, Falguni; Golden, Joseph W.; Swenson, Rolf E.; Smith, Darci R.; Bocan, Thomas M. (Molecular Imaging & Biology, 2018)
Purpose: The association of Zika virus (ZIKV) infection and development of neurological sequelae require a better understanding of the pathogenic mechanisms causing severe disease. The purpose of this study was to evaluate the ability and sensitivity of positron emission tomography (PET) imaging using [18F]DPA-714, a translocator protein (TSPO) 18 kDa radioligand, to detect and quantify neuroinflammation in ZIKV-infected mice.Procedures: We assessed ZIKV-induced pathogenesis in wild-type C57BL/6 mice administered an antibody to inhibit type I interferon (IFN) signaling. [18F]DPA-714 PET imaging was performed on days 3, 6, and 10 post-infection (PI), and tissues were subsequently processed for histological evaluation, quantification of microgliosis, and detection of viral RNA by in situ hybridization (ISH).Results: In susceptible ZIKV-infected mice, viral titers in the brain increased from days 3 to 10 PI. Over this span, these mice showed a two- to sixfold increase in global brain neuroinflammation using [18F]DPA-714 PET imaging despite limited, regional detection of viral RNA. No measurable increase in ionized calcium binding adaptor molecule 1 (Iba-1) expression was noted at day 3 PI; however, there was a modest increase at day 6 PI and an approximately significant fourfold increase in Iba-1 expression at day 10 PI in the susceptible ZIKV-infected group relative to controls.Conclusions: The results of the current study demonstrate that global neuroinflammation plays a significant role in the progression of ZIKV infection and that [18F]DPA-714 PET imaging is a sensitive tool relative to histology for the detection of neuroinflammation. [18F]DPA-714 PET imaging may be useful in dynamically characterizing the pathology associated with neurotropic viruses and the evaluation of therapeutics being developed for treatment of infectious diseases.